Regulation of Bone Marrow Angiogenesis by Osteoblasts during Bone Development and Homeostasis - Schipani, Ernestina; Wu, Colleen; Rankin, Erinn B.; Giaccia, Amato J. (Frontiers in Endocrinology, 2013)
Bone marrow is a highly heterogeneous and vascularized tissue. The various cell types populating the bone marrow extensively communicate with each other, and cell-to-cell cross talk is likely to be essential for proper bone development and homeostasis. In particular, the existence of osteogenesis and angiogenesis coupling has been recently proposed. Despite its high degree of vascularization, a gradient of oxygenation is present in the bone marrow, and the endosteal surface of cortical bone appears to be among the most hypoxic areas in the body. Oxygen (O2) is both an essential metabolic substrate and a regulatory signal that is in charge of a specific genetic program. An important component of this program is the family of transcription factors known as hypoxia-inducible factors (HIFs). In this Perspective, we will summarize our current knowledge about the role of the HIF signaling pathway in controlling bone development and homeostasis, and especially in regulating the crosstalk between osteoblasts, progenitor cells, and bone marrow blood vessels.